Atomic layer deposition of Pt nanoparticles onto Co/MoN nanoarrays for improved electrochemical detection of H2O2. Issue 4 (16th December 2022) - Liu, Jinzheng; Li, Xue; Cheng, Lidi; Sun, Junwei; Xia, Xiaomin; Zhang, Xiaoyan; Song, Yanyan; Sun, Deshuai; Sun, Jian; Zhang, Lixue
Abstract : A Pt@Co/MoN sensing platform was realized by atomic layer deposition of trace Pt onto a Co/MoN support, and the unique nanostructure endows it with a promising electrochemical detection capability towards H2 O2 in real samples and in living cells. Abstract : The design and preparation of advanced nanocatalysts for the sensitive electrochemical detection of H2 O2 is of great significance. Herein, a facile Pt@Co/MoN sensing platform was fabricated by depositing Pt nanoparticles onto Co/MoN nanoarrays using atomic layer deposition (ALD) technology. Benefitting from the unique nanostructure and the strong interaction between Pt and the nitride support, the prepared Pt@Co/MoN exhibited excellent performance in the electrochemical detection of H2 O2 . This work provides an interesting strategy to fabricate low-Pt electrocatalysts on a nanoarray support for future applications in electroanalysis.